Analysis of Social Capital Determinants and Collective Action on Community Income Levels in Bilebante Tourism Village, Central Lombok - Agustiani, Eka; Yuniarti, Titi; Manan, Abdul; Ismiwati, Baiq; Astuti, Endang; Windayani, Baiq Nurul (Indonesian Journal of Advanced Research, 2026)
In the development of a tourism village, the primary focus is on the active participation of residents, which is closely linked to their social ties. The concept of social capital reflects the dynamics of community life where members collaborate efficiently to realize shared aspirations. The purpose of this study is to examine how social capital through collective action impacts the income level of the community in Bilebante Village. Social capital, which consists of components of trust, social networks, norms, and participation in rural economic development. This study uses the SEM-PLS 4 program. Structural equation modeling analysis is used to determine the relationship between variables. The results show that social capital and collective action have a significant positive effect of 95% on the income level of the community in Bilebante Village. Bilebante Village has succeeded in utilizing its social capital effectively by utilizing collective efforts to build and develop village potential, so that almost all residents can enjoy the development of Bilebante Village into a tourism village. These findings indicate that social capital and increased collective action can be an effective strategy in improving economic welfare in Bilebante Tourism Village.